Peningkatan pemahaman konsep makna keberagaman melalui model pembelajaran mind mapping pada peserta didik kelas iii sekolah dasar - Lathifah Lathifah; Hadiyah Hadiyah; Fadhil Purnama Adi (Didaktika Dwija Indria, 2019)
Abstract. The purpose of this research was to improve understanding concept the meaning of diversity by using mind mapping learning model. This research is Classroom Action Research with two cycles. The subjects of this research were teacher and students of the 3th students at SDIT Nurul Islam Tengaran, totalling 26 students which consist 12 male students and 14 female students at 2018/2019 academic year. This research uses data collection techniques in the form of interviews, observations, tests, and analysis document with data analysis of source triangulation, technique triangulation and content validity. The analysis of the data used is the interactive analysis model of Miles-Huberman. The first cycle resulting in a percentage of 46,15% in classical, and the study continued with the second cycle with the percentage of 80,77% in classical terms. The conclusion of this research, that understanding concept the meaning of diversity on 3th students of SDIT Nurul Islam Tengaran in the 2018/2019 academic year can be improved through the mind mapping learning model.